To transform the function \( f(x) = 3^x \) into the form \(-f(3x-2) + 1\), we can follow these steps:
Step 1
Identify the original function: \[ f(x) = 3^x \]
Step 2
Substitute \(3x - 2\) into \(f\): \[ f(3x - 2) = 3^{(3x - 2)} \]
Step 3
Apply the negative sign: \[ -f(3x - 2) = -3^{(3x - 2)} \]
Step 4
Add 1: \[ -f(3x - 2) + 1 = -3^{(3x - 2)} + 1 \]
So, the final transformation you are looking for is: \[ -f(3x - 2) + 1 = -3^{(3x - 2)} + 1 \]
Summary of Steps
- Step 1: Start with \( f(x) = 3^x \)
- Step 2: Find \( f(3x - 2) \) which results in \( 3^{(3x - 2)} \)
- Step 3: Apply the negative to get \(-3^{(3x - 2)}\)
- Step 4: Add 1 to be \(-3^{(3x - 2)} + 1\)
Conclusion
The order of operations shows that the correct transformation from \( f(x) = 3^x \) to \(-f(3x-2) + 1\) results in: \[ -f(3x - 2) + 1 = -3^{(3x - 2)} + 1 \]
This means the transform includes these correct intermediate results:
- \( 3^{(3x-2)} \)
- \(-3^{(3x-2)}\)
- \(-3^{(3x-2)} + 1\)
From the options provided, the correct step results are:
- Option: \(-3^{(3x-2)} + 1\), which represents the final function form.
It seems that the other transformations within your provided options (e.g., \(-3(^(3x-2))\), etc.) are either incorrect steps or not relevant to the required transformation sequence.